Value of Time in the Context of Communications Services - Kalevi Kilkki; Heikki Hämmäinen (International Telecommunications Society (ITS), 2019)
There is a long tradition of studies using the concept of the value of time (VoT) to assess human behavior in diverse situations. The underlying assumption in most of the studies is that when different activities are available, a rational person selects the activity that provides the highest value or utility for her. However, two major restrictions affect the selection: time and money. Thus, the selection process needs to take into account the average value created over a period of time and the (possible) money spent during the activity. In practice, this selection process is complicated and arduous to model accurately. There is an obvious need in many fields to predict how people behave, how they appreciate different situations, and how they allocate their time, which has led to extensive scientific literature. For instance, Jacoby et al. (1976), Concas & Kolpakov (2009), Small (2012), and Jara-Díaz & Rosales-Salas (2017) offer valuable overviews on the history and terminology related to the value of time. Although some interesting VoT papers were published already in the 1940s, the first wide-ranging treatment of the value of time was Gary S. Becker's 'A Theory of the Allocation of Time' published in 1965. Becker's paper is still, by far, the most cited VoT paper. Other important, early VoT papers include Beesley (1965), DeSerpa (1971), and Evans (1972)...
Keywords: 330